2005
DOI: 10.1590/s0004-282x2005000500029
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic prolactinoma: case report with immunohistochemical assessment for p53 and Ki-67 antigens

Abstract: -Pituitary carcinomas are rare neoplasms characterized by craniospinal and/or systemic metastases originated from the pituitary. Their histopathology is frequently indistinguishable from that of benign adenomas. The development of markers that better reflect their behavior is desirable. We present the case of a 47 year-old man with a pro l a c t i n -s e c reting macroadenoma who was submitted to surgeries, cranial radiation therapy, and bromocriptine treatment, but evolved to a fatal outcome after the disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It may be nevertheless considered aggressive a pituitary adenomas when there is a change in the behavior of a previous adenoma. Some authors [4,19] suggest that primary tumors with mitotic activity, as with increased (>3%) MIB-1 labeling index, and/or p53 immunoreactivity, should be defined as 'aggressive adenomas' to denote their aggressive potential and indicating a possibility for future malignant transformation [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be nevertheless considered aggressive a pituitary adenomas when there is a change in the behavior of a previous adenoma. Some authors [4,19] suggest that primary tumors with mitotic activity, as with increased (>3%) MIB-1 labeling index, and/or p53 immunoreactivity, should be defined as 'aggressive adenomas' to denote their aggressive potential and indicating a possibility for future malignant transformation [6].…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 140 cases of pituitary carcinoma were reported in an extensive review of the British literature up to 2005 [6], and additional 10 cases have been reported afterwards [1,2,[4][5][6][7][8][12][13][14][15][16][17][18][19][20][21] (table 1). Pituitary carcinomas have no gender difference and are diagnosed at a mean age of 44 years, with a latency period of 7 years after the initial diagnosis of a pituitary tumor [1,6].…”
Section: Epidemiologymentioning
confidence: 99%
“…Eighteen % and 38% cDNAs were differentially expressed by over 15-fold in the benign and malignant breast tumor cell lines, respectively. Amongst the cDNAs expressed at a higher level in the R37-OPN cells than in the R37 cells were previously characterized breast cancer-associated genes such as TPTI [ 14 ], ARNT [ 15 ], CSFIR [ 16 ], MDM2 [ 17 ], CD44 [ 18 ], Cxcr4 [ 19 ], RAN GTPase [ 20 ], cytokeratin 20 (CK20) [ 21 ], Ki67 [ 22 ], with fold increases of 8, 8, 9, 9, 11, 23, 25, 32, and 45, respectively. Amongst the cDNAs expressed at a lower level in R37-OPN cells were previously characterized cancer suppressor genes PTEN [ 23 ], ATM [ 24 ] and BRCA1 associated protein 1 [ 24 ] with decreases of 19, 23 and 23 fold, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Pituitary tumours, in majority of cases benign adenomas, account for 10-25% of intracranial tumours, their prevalence in the general population being 0. 02% [1,2], Anatomically, these tumours are classified as microadenomas (diameter<1cm) or ma croadenomas (diameter 21 cm) [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, pituitary tumours may be accompanied by hormonal activity or symp toms of "mass effect", such as invasion of the surrounding tissues (e. g. supra-sellar extension, sinus cavernous invasion and optic nerve compression), causing visual disturbances or headache. Compression of non-tumour pituitary results in varying degrees of hypopituitarism [2], Based on physical examination and blood hormone levels, pituitary tumours can be broadly classified as either functioning (FPA) or non-functioning pituitary adenomas (NFPA) -comprising approximately 30% of all ade nomas [1]. In about 10% of autopsies small pituitary adenomas are found, most of them having had no clinical manifestation [3].…”
Section: Introductionmentioning
confidence: 99%